Hukum Mengenai Hubungan Penjualan Online Diberbagai Ekspedisi - Juliyanti Nathasya; Rina Apriyani (Peneliti.net, 2023)
According to Law Number 11 of 2008 concerning Information and Electronic Transactions. Government Regulation of the Republic of Indonesia Number 82 of 2012 concerning the Implementation of Electronic Systems and Transactions. The purpose of this research is to find out how to sell online in various expeditions. The type of research used in this research is descriptive quantitative research. In descriptive research, it is necessary to obtain a complete and accurate description of a situation. The result of this analysis and research is that we must understand how the sales system in various expeditions is in accordance with applicable legal provisions. must also know the various types of expeditions for online sales. The main purpose of online sales is to increase sales and reach a wider market. This can be a pretty accitive marketing strategy in digital commerce. Create interesting content so that the product can be well known and remembered by consumers.